Synergy of flocculation and flotation for microalgae harvesting using aluminium electrolysis. (June 2017) - Shi, Wenqing; Zhu, Lin; Chen, Qiuwen; Lu, Ji; Pan, Gang; Hu, Liuming; Yi, Qitao
Graphical abstract: Highlights: Electro-flocculation is a rapid and efficient way to harvest microalgae. Microalgae flocs formed in a snowballing style. Phosphate decrease benefits microalgae based wastewater treatment. Abstract: Microalgae are often used as feedstock for renewable biofuel production and as pollutant up-takers for wastewater treatment; however, biomass harvesting still remains a challenge in field applications. In this study, electro-flocculation using aluminium electrolysis was tested as a method to collect Chlorella vulgaris . The electrolysis products were positively charged over a wide pH range below 9.5, which gave them a flocculation potential for negatively charged microalgae. As flocculants were in-situ generated and gradually released, microalgae flocs formed in a snowballing mode, resulting in the compaction of large flocs. When higher current density was applied, microalgae could be harvested more rapidly, although there was a trade-off between a higher energy use and more residual aluminium in the culture medium. Benefits of this flocculation method are twofold: the phosphate decrease in post-harvesting could improve nutrient removal in microalgae based wastewater treatment, while the ammonium increase may favor microalgae recovery for medium recycling.